FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN IBU HAMIL TRIMESTER KETIGA DALAM MENGHADAPI PERSALINAN SAAT PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS LIMO TAHUN 2022 - Muhammad Zein Malawat (2022)
One of the most important periods for women in their life cycle is pregnancy. Physical and psychological changes can be a stressor, causing anxiety in pregnant women. Anxiety can cause stunted fetal growth, increase the risk of miscarriage, low birth weight, premature birth, and can cause the APGAR score at birth to decrease. Maternal and infant mortality increased during the COVID-19 pandemic. Different results were found in studies regarding the level of anxiety of pregnant women, especially during the COVID-19 pandemic, there was an increase in the incidence of anxiety in pregnant women when compared to the incidence before the pandemic. This study aims to determine the factors that influence the anxiety level of third trimester pregnant women in facing childbirth during the COVID-19 pandemic. This type of research uses an observational analytical study with a cross- sectional design. A total of 38 samples of third trimester pregnant women were taken using the Consecutive Sampling technique. The results of this study indicate that there is a relationship between knowledge about COVID-19 (p-value 0.000, OR : 16,667, 95% CI : 2,835 - 97,966), social support (p-value 0.018, OR : 6,818, 95% CI : 1,238 - 37,544), economic status (p-value 0.017, OR : 7,700, 95% CI : 1,609 - 36,860) with the level of anxiety of pregnant women. The most dominant factor in influencing the level of anxiety is knowledge about COVID-19 (p-value 0.002, OR : 16,667, 95% CI: 2.835 - 97.966). Pregnant women with less knowledge about COVID-19 have a higher risk of experiencing severe anxiety.